(untitled) (Tanzania Medical Journal, 2021)
Background Immunization is among the most important public health interventions against common childhood diseases. However, a missed opportunity for vaccination (MOV), may hamper the progress made in reducing childhood illness through vaccination. Knowing the magnitude and contributing factors for MOV, is essential for planning and executing preventive measures; however, these factors are not well elucidated in the Tanzania context. Broad Objective To determine the magnitude and factors for MOV among children under five-years old admitted at Mwananyamala hospital. Methodology We conducted a hospital-based, cross-sectional descriptive study among children under-five year old who were admitted at Mwananyamala hospital and their respective care givers from October to November 2018. An interview-guided questionnaire was used to collect data from the caregivers. The childhood immunization history was obtained from the immunization cards. Data were analyzed using Statistical Package for Social Sciences (SPSS version 20). Results A total of 209 caretakers and their respective children were enrolled in the study. Thirty-eight (18.2%) had MOV, and among the missed vaccines, the second dose of measles and rubella was the most missed vaccine (45.5%). Identified factors for MOV were unavailability of the vaccine on the day of vaccination 12 (31.3%), the child being sick on the day of vaccination 10(26.3%), due date forgotten 8 (20.8%), not informed on when to return for vaccination 7(18.1%), and no money for transport to vaccination center 1 (2.7%). Conclusion and recommendation The magnitude of missed opportunity for vaccination is still high among hospital admitted children. Vaccine procurement and distribution as well as improved communication among caretakers and health personnel should be more strengthened to reduce the number of children who are missing vaccines. Keywords: Missed opportunity for vaccination, Children, Under-five, Dar es Salaam.